Injury prevention in elite soccer: perceptions and strategies of Brazilian soccer teams - Cassiolato de Freitas, F.; Fujisawa, D. S.; de Souza Guerino Macedo, C. (Journal of Physical Education and Sport, 2020)
Background: The injury preventive strategies of Brazilian soccer teams has not been completely established in the literature and few studies have investigated those practices in elite soccer teams around the world. Objective: To identify the injury prevention strategies and practices adopted in Brazilian soccer teams. Methods: Setting: cross-sectional study. Participants: Seventy-two Brazilian soccer teams.